2015
DOI: 10.1038/ncomms7510
|View full text |Cite
|
Sign up to set email alerts
|

Symportin 1 chaperones 5S RNP assembly during ribosome biogenesis by occupying an essential rRNA-binding site

Abstract: During 60S biogenesis, mature 5S RNP consisting of 5S RNA, RpL5 and RpL11, assembles into a pre-60S particle, where docking relies on RpL11 interacting with helix 84 (H84) of the 25S RNA. How 5S RNP is assembled for recruitment into the pre-60S is not known. Here we report the crystal structure of a ternary symportin Syo1–RpL5-N–RpL11 complex and provide biochemical and structural insights into 5S RNP assembly. Syo1 guards the 25S RNA-binding surface on RpL11 and competes with H84 for binding. Pull-down experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 30 publications
2
73
0
1
Order By: Relevance
“…A specific feature of LSU assembly is the incorporation of a preformed 5S RNP ( Figure 2J) comprising the 5S RNA and the rproteins uL5 and uL18. Formation of the 5S RNP is facilitated by the transport adaptor Syo1, which couples nuclear import of uL5 and uL18 with 5S rRNA association [90,91]. The subsequent incorporation of the 5S RNP module involves the Rpf2-Rrs1 heterodimer and has already occurred within the Nsa1-defined particle [25,86,[92][93][94] (Figure 2K).…”
Section: Assembly Of the Lsumentioning
confidence: 99%
“…A specific feature of LSU assembly is the incorporation of a preformed 5S RNP ( Figure 2J) comprising the 5S RNA and the rproteins uL5 and uL18. Formation of the 5S RNP is facilitated by the transport adaptor Syo1, which couples nuclear import of uL5 and uL18 with 5S rRNA association [90,91]. The subsequent incorporation of the 5S RNP module involves the Rpf2-Rrs1 heterodimer and has already occurred within the Nsa1-defined particle [25,86,[92][93][94] (Figure 2K).…”
Section: Assembly Of the Lsumentioning
confidence: 99%
“…It has been shown that karyopherins or chaperones interact with ribosomal proteins to maintain their solubility and also facilitate their loading into nascent ribosomal subunits (33)(34)(35)(36)(37)(38)(39)(40)(41)(42).…”
Section: Figure 2 the Function Of Bcp1 Is Tightly Connected With Manmentioning
confidence: 99%
“…Rrb1 has direct interaction with Rpl3 (uL3), and overexpression of Rrb1 increased the level and nuclear accumulation of Rpl3 (36). Syo1 facilitates coimport of Rpl5 (uL18) and Rpl11 (uL5) and chaperones 5S RNP assembly (33,38). Acl4 is a chaperone of Rpl4 (uL4) and accompanies Rpl4 from the cytoplasm to the loading onto the pre-60S in the nucleus (39,41).…”
Section: Bcp1 Is a Chaperone Of Rpl23 And Required To Maintain Thementioning
confidence: 99%
“…4A,B; Leidig et al 2014). Notably, rRNA H84 engages in a native-like interaction with protein uL5 of the 5S RNP, indicating that it may serve as an initial docking site during assembly (Leidig et al 2014;Calviño et al 2015).…”
Section: The Architecture Of the Immature Central Protuberance In Nucmentioning
confidence: 99%